Identification and Characterization of Genes Encoding the Hydroxypyruvate Reductases in Chlamydomonas Reveal Their Distinct Roles in Photorespiration - Shi, Menglin; Zhao, Lei; Wang, Yong (Frontiers in Plant Science, 2021)
Photorespiration plays an important role in maintaining normal physiological metabolism in higher plants and other oxygenic organisms such as algae. The unicellular eukaryotic organism Chlamydomonas is reported to have a different photorespiration system from that in higher plants, and only two out of nine genes encoding photorespiratory enzymes have been experimentally characterized. Hydroxypyruvate reductase (HPR), which is responsible for the conversion of hydroxypyruvate into glycerate, is poorly understood and not yet explored in Chlamydomonas. To identify the candidate genes encoding hydroxypyruvate reductases in Chlamydomonas (CrHPR) and uncover their elusive functions, we performed sequence comparison, enzyme activity measurement, subcellular localization, and analysis of knockout/knockdown strains. Together we identify five proteins to be good candidates as CrHPRs, all of which are detected with the activity of hydroxypyruvate reductase. CrHPR1, a NADH-dependent enzyme in mitochondria, may function as the major component of photorespiration, and deletion of CrHPR1 causes severe photorespiratory defects. CrHPR2 takes parts in the cytosolic bypass of photorespiration as the compensatory pathway of CrHPR1 for the reduction of hydroxypyruvate. CrHPR4, with NADH as the cofactor, may participate in photorespiration by acting as the chloroplastidial glyoxylate reductase in glycolate-quinone oxidoreductase system. Therefore, our results reveal that the CrHPRs are far more complex than previously recognized, and provide a greatly expanded knowledge base for studies to understand how CrHPRs perform their functions in photorespiration. These will facilitate both the modification of photorespiration and genetic engineering for crop improvement by synthetic biology.